The class - Dowell, Frances O'Roark (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2019)
Sixth grade is a MOST confusing time. Best friends aren't friends anymore. Worst enemies suddenly want to be partners in crime. And classmates you thought you knew have all sorts of surprising stuff going on. The kids in Mrs. Herrera's class are dealing with all these things and more--specifically, three more: 1. There's a new girl who just seems to be spying on them all and scribbling things in a notebook. Maybe she IS a spy? 2. Someone is stealing all of Mrs. Herrera's most treasured items. 3. Their old classmate, Sam, keeps showing up and no one knows why...until they do. Which leads to a fourth problem. But we can't tell you about that yet. The twenty kids in Mrs. Herrera's classroom can, though, and they do. Every. Single. One. Of. Them.